Gender Equality Challenges in Afghanistan - Juwarti Hafsah; Yon Machmudi; Maria Puspitasari; Sya’roni Rofii (Postgraduate, University of Mataram, 2025)
This study aims to analyze the impact of restricting women's rights on the development of civilization, focusing on the condition of women in Afghanistan after the Taliban regained power. The method used is qualitative analysis with a descriptive approach based on secondary data from international reports, scholarly articles, and reliable news sources. The study results show that restrictions on women's rights and roles in various aspects of life, such as education, employment, and social participation, negatively affect societal and civilizational progress. The discussion reveals that the systemic injustice experienced by women in Afghanistan not only suppresses individual rights but also slows down the country's social and economic development. In conclusion, policies that limit women's roles can hinder or even halt the progress of civilization, highlighting the need for global efforts to promote gender equality and the protection of human rights.